Remote self-administration of digital cognitive tests using the Brief Assessment of Cognition: Feasibility, reliability, and sensitivity to subjective cognitive decline - Atkins, Alexandra S.; Kraus, Michael S.; Welch, Matthew; Yuan, Zhenhua; Stevens, Heather; Welsh-Bohmer, Kathleen A.; Keefe, Richard S. E. (Frontiers in Psychiatry, 2022)
Cognitive impairment is a common and pervasive feature of etiologically diverse disorders of the central nervous system, and a target indication for a growing number of symptomatic and disease modifying drugs. Remotely acquired digital endpoints have been recognized for their potential in providing frequent, real-time monitoring of cognition, but their ultimate value will be determined by the reliability and sensitivity of measurement in the populations of interest. To this end, we describe initial. Participants were 69 older adults (age 55+), including 20 individuals with subjective cognitive decline (SCD). To allow comparison between remote (home) and site-based testing, participants completed 2 testing sessions 1 week apart. Results for three of four cognitive domains assessed demonstrated equivalence between remote and site-based tests, with high cross-modality ICCs (absolute agreement) for Symbol Coding (ICC=.75), Visuospatial Working Memory (ICC=.70) and Verbal Fluency (ICC>.73). Group differences in these domains were significant and reflected sensitivity to objective cognitive impairment in the SCD group for both remote and site-based testing (p<.05 for all). In contrast, performance on tests of verbal episodic memory suggested inflated performance during unmonitored testing and indicate reliable use of remote cognitive assessments may depend on the construct, as well as the population being tested.